A new diketopiperazine derivative from a deep sea-derived Streptomyces sp. SCSIO 04496. Issue 2 (17th January 2016) - Luo, Minghe; Tang, Guiling; Ju, Jianhua; Lu, Laichun; Huang, Hongbo
Abstract : A new diketopiperazine (DKP) derivative, (6 R, 3 Z )-3-benzylidene-6-isobutyl-1-methyl piperazine-2, 5-dione (1 ), as well as five known DKPs2 –6 was isolated from a deep sea-derived Streptomyces sp. SCSIO 04496. The structure of1 was elucidated using a combination of 1D and 2D NMR, HR-ESI-MS and chiral-phase HPLC techniques. Compounds1 –6 did not show cytotoxic activity at a concentration of 100 μM in bioactivity assay. Abstract :